2015
DOI: 10.1177/1934578x1501001233
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Cordyceps cicadae

Abstract: One new bifuran derivative (1), together with fourteen known compounds, were isolated from Cordyceps cicadae X. Q. Shing. The known compounds included nine nucleosides, uracil (2), uridine (3), 2'-deoxyuridine (4), 2'-deoxyinosine (5), guanosine (6), 2'-deoxyguanosine (7), thymidine (8), adenosine (9), and 2'-deoxyadenosine (10); three amino acids tryptophan (11), phenylalanine (12), and tyrosine (13); and two dopamine analogues N-acetylnoradrenaline (14) and its dimer, trans-2-(3',4'-dihydroxyphenyl)-3-acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In contrast to other Cordyceps fungi, the caterpillar fungus O. sinensis has a highly repetitive genome with a limited number of genes and BGCs ( Figure 3 A) [ 24 ]. Besides the reported bioactive constituents like nucleosides, sterols and polysaccharides [ 18 , 67 , 68 , 69 ], a few compounds have been identified from this fungus with different activities such as the aurantiamides cordyceamides A and B with unclear activity/toxicity [ 70 ], the cyclodipeptide cordycedipeptide A with cytotoxicity [ 71 ], and the cyclodipeptide cordysinins with antioxidant activity [ 69 , 72 ]. Overall, the reputed health benefits of this fungus are still unclear [ 73 ].…”
Section: Unknown Mycotoxins May Be Produced By Cordycepsmentioning
confidence: 99%
“…In contrast to other Cordyceps fungi, the caterpillar fungus O. sinensis has a highly repetitive genome with a limited number of genes and BGCs ( Figure 3 A) [ 24 ]. Besides the reported bioactive constituents like nucleosides, sterols and polysaccharides [ 18 , 67 , 68 , 69 ], a few compounds have been identified from this fungus with different activities such as the aurantiamides cordyceamides A and B with unclear activity/toxicity [ 70 ], the cyclodipeptide cordycedipeptide A with cytotoxicity [ 71 ], and the cyclodipeptide cordysinins with antioxidant activity [ 69 , 72 ]. Overall, the reputed health benefits of this fungus are still unclear [ 73 ].…”
Section: Unknown Mycotoxins May Be Produced By Cordycepsmentioning
confidence: 99%
“…Cordyceps cicadae, a Chinese traditional food fungus, has antioxidation, anti-inflammation [1], blood sugar regulation (Li et al, 2018), renal function improvement [2,3], liver protection [4], and neuroprotection [5] properties. The functional components of C. cicadae are adenosine, N(6)-(2-Hydroxyethyl) adenosine (HEA), and polysaccharides [6,7], which are proven to have antioxidation, anti-inflammatory, and anti-aging properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a noted traditional Chinese medicine, cicada flowers have been applied in therapies for fatigue, night perspiration, fever, childish convulsion, palpitation, and dizziness for a long time. In addition, modern pharmacological research has demonstrated that cicada flowers possess antitumor, antifatigue, anti-inflammatory, immunomodulatory, analgesic, , renoprotective, and sedative properties. , Many bioactive compounds, including polysaccharides, , myriocin, ergosterol peroxide, and nucleosides, have been isolated from cicada flowers.…”
Section: Introductionmentioning
confidence: 99%
“…The wild cicada flowers are in great market demand nowadays because of their potent bioactivities, but they are expensive because of their rarity in nature and the difficulty of artificial cultivation. To satisfy the large consumption demand of cicada flowers, two major artificial culture techniques, solid-state fermentation and submerged fermentation, have been developed . However, several studies have reported that constituent differences exist between the fermented products of Isaria cicadae and wild cicada flowers .…”
Section: Introductionmentioning
confidence: 99%